Assessment of Food Security in the East Kazakhstan Region - Aigerim Duisenbekova; Alina Daniłowska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article assesses the food security of one region of Kazakhstan - the East Kazakhstan region. In the analyses, criteria such as the level of the region’s food independence, the degree of satisfaction of the population’s physiological needs in basic food, and the level of economic availability of food were applied. The research has shown that the food security in the East Kazakhstan region was at an acceptable level. However, some threats to food security were identified, including: a high level of income differentiation among the households of the East Kazakhstan region, an increase in the price index for food products, and a significant proportion of the population with incomes below the subsistence minimum. The results of the evaluation can be useful for creating agri-food policy measures that will ensure, maintain and improve the level of food security at both a regional and national level.